Readiness of Islamic Religious Education Teachers to Implement the Independent Curriculum Assessment at Elementary School 99, Bengkulu City - Lidya Lidya; Eva Bonita; Wiwinda Wiwinda; Yosi Yulizah (International Journal on Advanced Science, Education, and Religion, 2025)
This study aims to describe teacher readiness in implementing the Independent Curriculum assessment. A descriptive qualitative approach was used at SDN 99, Bengkulu City, using data from Islamic Religious Education (PAI) teachers and the principal. The results indicate that teachers at SDN 99, Bengkulu City, have basic readiness to implement the Independent Curriculum assessment. This is evident in their understanding of assessment concepts, including diagnostic, formative, and summative assessments, and their efforts to implement them in their lessons. Teachers have also developed lesson plans through teaching modules that include learning objectives, CP, ATP, and assessment plans. Furthermore, teachers demonstrate a positive attitude toward curriculum changes and strive to implement various assessment methods, such as observation, assignments, discussions, and tests, to assess student learning processes and outcomes. However, the implementation of these assessments has not been fully optimized due to various obstacles, such as time constraints, administrative burdens, lack of technical understanding, and skills in documentation and feedback. Formative assessments have not been well documented, while summative assessments are still more dominant than other types of assessment. Therefore, it is necessary to improve teacher competency through continuous training, mentoring, and strengthening learning communities.